Políticas educacionais, avaliação e desempenho: revisitando a escola municipal amarela e a escola municipal branca - França, Nara Rubia Maia (2016)
This research is a result of the study doctoral thesis Lydia Godoy Milano, under the educational policies, evaluation and performance: Municipal Web Goiânia Education. This thesis was presented in 2012, the Graduate Program in Education at the Catholic University of Goiás - PUC-GO. In this sense, the objective of our work was to return to schools surveyed by that thesis to understand why one of the schools, ―White Municipal School‖, had reached one of the worst grades in Brazil IDEB test, despite having both physical structures as pedagogical considered appropriate for a good education; at the same time, however, to understand the reason (s) of another school, ―Yellow Municipal School‖, having obtained one of the best ratings in the same evaluation process, though having physical characteristics and poor teaching. So we try to verify the reasons for this paradox, between physical and educational structures and verify that the last evaluation both have achieved or not the targets set by the assessments of IDEB. Our study concluded that social relations that occur in any environment, either within the classroom or other indoor environment of schools are built and rebuilt on a daily basis. On the face of it, these social interactions enable, in socio-historical perspective, think of a human being in constant construction and transformation, as well as understand that these relationships can influence the academic performance of their students. This is what was observed in this research, including from a significant change in IDEB of both schools.